Ablaze the story of the heroes and victims of Chernobyl - Read, Piers Paul 1941- (Random House, 1993)
Early on the morning of April 26, 1986, the nuclear reactor at the fourth unit of the V. I. Lenin power station at Chernobyl exploded. In the terror and panic that followed, an engineer grabbed a dosimetrist to ask for a radiation level and was told it was off the dial. "With a dread feeling in his heart, Sasha Yuvchenko at last realized that they were all almost certainly doomed to die...." Piers Paul Read's enthralling account of this disaster and its aftermath is filled with acts of courage - as well as bumbling confusion, secrecy, lies and cover-ups. To chronicle the catastrophe, he interviewed the engineers and operators who were on duty during the fateful test that was being conducted on the night of April 25; talked to the director of the power station, who was serving a ten-year sentence for negligence; and visited the hitherto top-secret institutes once run by Beria's Ministry of Medium Machine Building: the Kurchatov Institute, Moscow's Hospital No
Keywords: Čornobyl‛s‛ka atomna elektrostancija; Geschichte 1986; Umwelt; Chernobyl Nuclear Accident, Chornobylʹ, Ukraine, 1986 -- Environmental aspects; Radiation injuries -- Ukraine -- Pryp'i͡atʹ; Radioactive pollution -- Ukraine -- Pryp'i͡atʹ; Umweltpolitik; Reaktorunfall; Strahlenschaden; Katastrophenmanagement; Tschernobyl; Sowjetunion